Performance Analysis of Graph Algorithms for Microgrid Protection - Saluja, Jasleen; Biswas, Swagata; Roy, Souvik; Swathika, O.V. Gnana (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
Microgrids are energy systems that consist of distributed energy sources and loads, which can operate in parallel with or independently from the main grid. The integration of renewable Energy System (RES) into microgrid causes the power flow to be bidirectional in nature. Reconfiguration of the microgrid could occur due to RES, load or utility grid connection or disconnection. Thus, conventional protection strategies are not applicable to microgrids and it is challenging for engineers to tackle any faulty issues. This paper proposes graph algorithms, such as the Kruskals and the Prim which aid in identifying the shortest path from a faulted point to the point of common coupling(PCC). Algorithms, such as Floyd Warshall and Djiktra’s algorithms ensure that only minimum portion of the network is disconnected during fault clearance.